Normal values of cervical vertebral measurements according to age and sex in CT - DENİZBAŞI ALTINOK, ARZU; AKOĞLU, HALDUN; ONUR, ÖZGE ECMEL (W B SAUNDERS CO-ELSEVIER INC, 2017)
Introduction: Atlantodental interval (ADI), basion-dental interval (BDI) and the thickness of prevertebral soft tissue (TOPST) measured in lateral cervical radiographs were reported to be useful indicators and indirect signs of underlying cervical spine injuries. However, cervical computed tomography (MDCT) is the firstmethod of imaging used in all trauma patients and upper normal limits (UNLs) of cervical distances according to age and sex are undetermined. Therefore, we aimed to calculate these metrics. Methods: 500 adult trauma patients with cervical MDCT at the time of admission were retrospectively selected. ADI, BDI, and TOPSTs were measured by two blinded researchers. Results: 488 cervical spine CT scans were reported to be normal and 12 has pathological findings. Mean ADI, BDI and TOPST of C1, C2, C6 and C7 were statistically significantly wider in males. In females, ADI and BDI were significantly narrower with the increase in age. In males, only ADI was significantly narrower, and TOPST of C6 and C7 vertebra were significantly wider with the increase in age. We found the optimal UNLs as follows: ADI 2.5mm, BDI 8.5mm, C1 6.5mm, C2 5.7mm, C3 6.3mm(6mmfor C1-3 for practical purposes), C4 11.7 and C5-7 17mm. Discussion: We believe that the increase in distances with age may be affected by the height losses of discs and vertebral bodies, formation of anterior osteophytes and regional kyphosis by age. Those results were compatible with the previous reports. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: Emergency department; Thickness of the prevertebral soft tissue; Prevertebral soft tissue thickness; Atlantodental interval; Predental space; Basion-dental interval; Computerized tomography; Reference value; Upper normal limit; TRAUMATIC OCCIPITOVERTEBRAL DISSOCIATION; RADIOLOGIC-DIAGNOSIS; LATERAL RADIOGRAPHS; SUPINE SUBJECTS; SHADOW; SPINE; NECK